Probiotics for broiler chickens in Brazil: systematic review and meta-analysis - Faria Filho, DE [UNESP]; Torres, KAA [UNESP]; Faria, DE; Campos, DMB [UNESP]; Rosa, PS [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2006)
This study evaluated the efficacy of probiotic utilization as growth promoters in broiler chicken feeding using systematic literature review and meta-analysis. Thirty-five studies were recovered by the systematic review, 27 of which met the following criteria to be included in the meta-analysis: (1) Brazilian studies published between 1995 and 2005; (2) probiotics administered in the diet without growth promoter; (3) results included performance data with the respective coefficient of variation. Meta-analysis have shown that the probiotics promoted better weight gain and feed conversion than the negative control (no antimicrobial) in the initial phase (1 to 20-28 days); nevertheless, results were similar in the total period (1 to 35-48 days). Weight gain and feed conversion were similar between probiotics and the positive control (with antimicrobial) both in the initial and in the total periods. Viability in the total period improved with the use of probiotics in comparison to the negative or positive controls. Sensitivity analysis showed that the results of meta-analysis were coherent. The funnel plots and the Egger regression method evidenced that the studies published in Brazil do not present biased results. It is possible to conclude that the probiotics are a technically viable alternative to antimicrobial growth promoters in broiler feeding. Nevertheless, further studies are necessary to identify eventual differences among the probiotics commercially available in Brazil.
Keywords: Birds; intestinal microflora; microorganism; performance